Alterations of NMDA receptor binding in various brain regions among 6-hydroxydopamine-induced Parkinsonian rats. (1st June 2014) - Wang, Qing; Li, Jin; Wei, Xiaobo; Liao, Jinchi; Xu, Yunqi; Lu, Tingting; Qin, Bing; Xie, Junqiang; Deng, Chao; Huang, Xufeng
Abstract : The N -methyl-d-aspartate (NMDA) system closely interacts with the dopaminergic system and is strongly implicated in the pathophysiological mechanisms and therapeutic paradigms of Parkinson's disease. This study aims to systematically investigate the changes of NMDA receptors in a wide range of brain structures 3 weeks after unilateral medial forebrain bundle lesion by 6-hydroxydopamine (6-OHDA). NMDA receptor distributions and alterations in the post-mortem rat brain were detected by [ 3 H] MK-801 binding autoradiography. In the 6-OHDA-induced Parkinsonian rat model, nigrostriatal dopaminergic neuron loss significantly mediated the decreased [ 3 H] MK-801 binding, predominantly in the hippocampus (−22.4%, p < 0.001), caudate putamen (−14.1%, p < 0.01), accumbens nucleus (−13.8%, p < 0.05), cingulate cortex (−13.4%, p < 0.001), posteromedial cortical amygdala (−14.5%, p < 0.01) and piriform cortex (−9%, p < 0.05) compared to the controls, while there was a profound reduction of tyrosine hydroxylase (TH) immunohistochemistry in the substantia nigra pars compacta. Alterations in [ 3 H] MK-801 in the specific brain regions related to cognitive functions may indicate that cognitive dysfunctions caused by 6-OHDA lesion were via the NMDA system. The downregulation of NMDA receptor binding in the present study provides indirect evidence for plasticity in the NMDA system in the rat brain. The present study improves our understanding of the critical roles of the NMDA receptors in treating neurodegenerative disorders, and implicates NMDA receptors as a novel therapeutic target in the treatment of Parkinson's disease.